1979
DOI: 10.1002/j.1551-8833.1979.tb04349.x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Organics Removal by Anion Exchange Resins

Abstract: Experimental evidence indicates that most of the organics that currently pass through conventional treatment can be removed using strongly basic anion exchange resins. Organics, measured as total organic carbon, were removed to below the limits of detection, as were the sulfates; the resins were regenerated using sodium chloride. <

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These resins became of concern after studies demonstrated the strong potential of anion exchange resins for removal of natural organic matter (NOM). Anion exchange resins are more effective for NOM removal than non-ionic resins, activated carbon, and cationic polymers (Anderson and Maier, 1979;Boening et al, 1980;Bolto et al, 2002). Ion exchange resins can also deal with micro-pollutants, such as pentachlorophenol, 2,4,6-trichlorophenol, 2,6-dichlorophenol and phenol (Li and Sengupta, 1998;Carmona et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These resins became of concern after studies demonstrated the strong potential of anion exchange resins for removal of natural organic matter (NOM). Anion exchange resins are more effective for NOM removal than non-ionic resins, activated carbon, and cationic polymers (Anderson and Maier, 1979;Boening et al, 1980;Bolto et al, 2002). Ion exchange resins can also deal with micro-pollutants, such as pentachlorophenol, 2,4,6-trichlorophenol, 2,6-dichlorophenol and phenol (Li and Sengupta, 1998;Carmona et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the effectiveness of these treatment processes, dissolved organic carbon (DOC) is commonly used as a surrogate for NOM. Both conventional polymeric anion exchange resins and a magnetic ion exchange (MIEX) resin have previously been evaluated for removing DOC and controlling the formation of DBPs. The major difference between these two classes of resins is their mode of treatment, i.e., conventional polymeric resins are used in a fixed-bed to treat filtered water, whereas MIEX resin is used in a completely mixed flow reactor to treat raw water.…”
Section: Introductionmentioning
confidence: 99%
“…Among ion exchange resins, polyacrylic, macroporous, strong-base anion exchange resins have been shown to be most effective for DOC removal ,, . In addition, previous work by the authors, consisting of laboratory-scale batch experiments and pilot-scale continuous-flow studies, showed that treatment of raw drinking water with MIEX resin was more effective than coagulation at removing DOC and reducing the formation of THMs and HAAs , .…”
Section: Introductionmentioning
confidence: 99%
“…Anion exchange resins have been reported to remove large quantities of NOM from natural waters (Boyer & Singer, 2005; Humbert et al, 2005; Bolto et al, 2002; Singer & Bilyk, 2002; Anderson & Maier, 1979). Generally, an anion exchange resin exchanges a chloride ion from a quaternary ammonium functional group for an organic anion.…”
Section: Introductionmentioning
confidence: 99%